The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2018
DOI: 10.1017/s002193201800038x
|View full text |Cite
|
Sign up to set email alerts
|

What affects utilization of malaria control services? A qualitative approach to understanding community perception in highly malarious Gadchiroli district, Maharashtra, India

Abstract: National Vector Borne Disease Control Programme (NVBDCP) data have shown that nearly half of all malaria deaths in India occur in tribal-dominated areas. The present study took a qualitative approach to understanding community perceptions and practices related to malarial infection and anti-malarial programmes. Twelve focus group discussions and 26 in-depth interviews of Accredited Social Health Activists (ASHAs) were conducted in nine villages in the district of Gadchiroli, Maharashtra state in India in June … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…A small section of the respondents also mentioned about the misuse of LLIN. Similar observations were revealed in the Gadchiroli study [ 8 ].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…A small section of the respondents also mentioned about the misuse of LLIN. Similar observations were revealed in the Gadchiroli study [ 8 ].…”
Section: Discussionsupporting
confidence: 91%
“…The size and geographical terrain of Mandla, the endemicity of malaria, weak socio-economic status and the ability to retain field staff were the key challenges considered by the project at the onset of the study. These barriers have been well observed in studies conducted in other areas having similar geo-climatic and socio-cultural environment [ 3 8 ]. In the local tribal communities, the treatment-seeking behaviour is poor and help is sought only when the situation becomes serious.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…This study also demonstrated that considerably more scheduled tribe households had malaria cases compared others social group households. The reasons for it may be the lifestyle of tribal communities, compounded by mass poverty in these communities [ 26 , 39 ]. Poor housing, engagement in outdoor activities, and outdoor sleeping habits are also common among rural and tribal communities and all these associated with malaria transmission in tribal areas [ 26 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence using AYUSH and THP for malaria was about 1.2%, similarly to the biomedical sector (1.2%). In a qualitative study in the district of Gadchiroli, Maharashtra state in India, widespread misconceptions about malaria and treatment by unquali ed traditional healers delayed effective treatment seeking [41]. The higher utilization of AYUSH and/or THP for fever or pyrexia of unknown cause, chronic pain in joints, arthritis, rheumatism or osteoporosis, generalized pain (stomach, headache, migraine, or other nonspeci c pain) than allopathic health care services, may emphasise their role in the provision of both acute and chronic care services.…”
Section: Discussionmentioning
confidence: 99%